Cardiac surgeryNeuropsychological changes after off-pump and on-pump coronary artery bypass surgery - Michalak, Alicja; Szyguła-Jurkiewicz, Bożena; Mościński, Mateusz; Muzyk, Piotr; Samborski, Konrad; Kłaczek, Bogumiła; Knapik, Piotr; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: A major problem in patients after cardiac surgery are cognitive decline. Aim of the study: 1 . To determine cognitive functions in patients undergoing surgical myocardial revascularisation with extracorporeal circulation (CABG), and without (OPCAB). 2. To determine factors affecting cognitive functions in early postoperative period in analysed group of patients. Material and methods: The analysis encompassed 160 consecutive patients undergoing elective surgical myocardial revascularisation in 2010-2011. Neuropsychological assessment was carried out one day before and five days after surgery using: Hospital Anxiety and Depression Scale (HADS), Rey Auditory Verbal Learning Test (AVLT), Benton Visual Retention Test (BVRT), Verbal Fluency Test FAS (Controlled Word Association Test), Trail Making Test (TMT), Digit Span Subtest, and Digit Symbol Test – Wechsler Adult Intelligence Scale (WAIS-R PL). Results : One hundred three of 160 patients, of whom 64 (62.1%) underwent CABG and 39 (37.9%) OPCAB, were qualified for the analysis. After surgery there was a significant decrease in results of Rey Auditory Verbal Learning Test (AVLT), Verbal Fluency Test (FAS), Digit Span Subtest and Digit Symbol Test in the group CABG and in results of AVLT after 30 minuts in group OPCAB. Multi-factor analysis revealed that an unstable disease course caused a decline in verbal skills, whilst surgery with extracorporeal circulation and carotid atherosclerosis had a negative, independent effect on visuomotor co-ordination and visuospatial operating memory. Conclusions: 1. In the group CABG cognitive decline regarded top-down attention, echoic memory, sensory procedural memory, recognition and immediate recall verbal symbols, verbal fluency, echoic and iconic learning ability, visual-motor coordination and the pace of information processing. In the group OPCAB cognitive decline was observed only with regard to delayed verbal memory, whilst visual memory improved. 2. The independent factors for cognitive decline are: unstable disease course (which lowers verbal fluency), surgery carried out with the classic method using extracorporeal circulation, and carotid atherosclerosis (which has a negative impact on visual-motor coordination and visuospatial operating memory).